Enabling technologies mitigating climate change: The role of dominant designs in environmental innovation ecosystems - Nylund, Petra A.; Brem, Alexander; Agarwal, Nivedita (Technovation, 2022)
Global warming is no longer a trend, but reality, which calls for the development of new technologies. In this paper, we thus identify antecedents of enabling technologies and study the patterns of emergence of new fields of eco-innovation. For this, we suggest a conceptual framework focusing on environmental technologies, specifically on their emergence as enabling technologies in innovation ecosystems. We test this framework using data of 136,059 citations to 13,510 patents of climate change mitigation technologies. Complex and complementary technologies tend to be more enabling for subsequent innovation, and this effect is amplified for environmental technologies that constitute dominant designs. Dominant designs generated through a collaborative process, on the other hand, rarely become enabling technologies. We also contribute to climate action by allowing governmental bodies and other investors to direct funding to those innovations that are most likely to make a lasting impact on global warming. In addition, managers and policy makers can foment the antecedents that are most important to incite the development of climate change mitigation technologies.
CRIS-Team Scopus Importer:2022-09-30
Keywords: Climate change; Dominant design; Eco-innovation; Environmental technologies; Innovation ecosystem; Technological innovation; Inklusion